Tagapagligtas, Ilaw, Kasama: Religiosity Among Filipino Domestic Workers in Hong Kong - Cernol-McCann, Betty; McCann, Dennis P.; Alvarez, Margaret Helen U. (Silliman Journal, 2022)
The plight of Filipino domestic workers abroad is much documented, especially in relation to economic pressures and psycho-emotional stresses. This paper investigated their patterns of coping by looking at their religious activities and attitudes towards their situation and life away from their families and country. A quantitative-qualitative study done in 2005 was supplemented by interviews made in 2009. In the 2005 study, the majority of the 121 respondents were college-educated, young adults, married with children, and had been working in Hong Kong for over a year. Many of those who indicated they were single had also left children in the Philippines. Similar demographics were characteristic of the 17 Filipinas interviewed in 2009, but this group was made up mostly of residents of Bethune House who had taken shelter there after having experienced significant difficulties with their employers. In the 2005 study, virtually all (118 out of the 121 respondents) reported attending church in Hong Kong—most of them of the Roman Catholic faith. Attending church is an activity that gives them inner peace and wholeness and also allows them a fellowship with other Filipinos. Prayers focused on practical problems, for example, personal health and family members’ health so that they could remain employed in Hong Kong, as well as the welfare of their employers and the Hong Kong economy. The religious person is one who has personal discipline and applies this discipline to life and circumstances. God is viewed as powerful above all things, tagapagligtas (Savior), ilaw (guiding light), kasama (companion). In the 2009 study, while the primary focus was on the respondents’ happiness or well-being in general, the importance of religiosity for them was evident in their ranking of God (Religion) as a source of happiness higher than family, friends, and work. It was confirmed that Filipina domestic workers derive much comfort and support from a strong and active faith that in their view is crucial for their survival in Hong Kong. This conclusion is offered in order to stimulate further research on the role of churches and religious institutions in supporting Filipinas who must work overseas to meet the needs of their families.